2021
DOI: 10.3389/fonc.2021.738477
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Ferroptosis-Related Signature Model Including mRNAs and lncRNAs for Predicting Prognosis and Immune Activity in Hepatocellular Carcinoma

Abstract: BackgroundFerroptosis is a novel form of regulated cell death involved in tumor progression. The role of ferroptosis-related lncRNAs in hepatocellular carcinoma (HCC) remains unclear.MethodsRNA-seq and clinical data for HCC patients were downloaded from The Cancer Genome Atlas (TCGA) Genomic Data Commons (GDC) portal. Bioinformatics methods, including weighted gene coexpression network analysis (WGCNA), Cox regression, and least absolute shrinkage and selection operator (LASSO) analysis, were used to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 101 publications
2
45
0
Order By: Relevance
“…Statistical analysis showed that this risk model has good robustness and predictive power and that it can independently predict OS in patients with HCC. Furthermore, the predictive accuracy of our signature surpassed that of the previously reported prediction signature of HCC dependent on FR-lncRNAs or FRGs (Liang et al, 2020;Chen et al, 2021;Liang Wang et al, 2021;Liang et al, 2021;Nie et al, 2021;Wan et al, 2021;Xu et al, 2021). The nomogram consisting of age, stage, and six FR-related lncRNA risk scores could be used to visually predict the OS of individual patients with HCC at 1, 3, and 5 years.…”
Section: Discussionmentioning
confidence: 64%
“…Statistical analysis showed that this risk model has good robustness and predictive power and that it can independently predict OS in patients with HCC. Furthermore, the predictive accuracy of our signature surpassed that of the previously reported prediction signature of HCC dependent on FR-lncRNAs or FRGs (Liang et al, 2020;Chen et al, 2021;Liang Wang et al, 2021;Liang et al, 2021;Nie et al, 2021;Wan et al, 2021;Xu et al, 2021). The nomogram consisting of age, stage, and six FR-related lncRNA risk scores could be used to visually predict the OS of individual patients with HCC at 1, 3, and 5 years.…”
Section: Discussionmentioning
confidence: 64%
“…Morever, many lncRNAs are involved in the progression of malignant tumors and tumor resistance, and have become new biomarkers and therapeutic targets in cancer diagnosis and treatment ( Wang et al, 2019a ). The excellent predictive ability of frlncRNAs in cancer has been confirmed in a variety of cancers ( Chen et al, 2021b ; Lu et al, 2021 ; Jin et al, 2021 ; Li et al, 2021 ). However, the mechanism of frlncRNAs in OSCC is still unclear.…”
Section: Discussionmentioning
confidence: 86%
“…Zi-An Chen et al developed a predictive and prognostic ferroptosis-related signature model based on 2 ferroptosis-related mRNAs (SLC1A5 and SLC7A11) and 8 ferroptosis-related lncRNAs (AC245297.3, MYLK-AS1, NRAV, SREBF2- AS1, AL031985.3, ZFPM2-AS1, AC015908.3, MSC-AS1) in HCC [ 116 ]. The findings revealed differences of tumor microenvironment and immune cell infiltration as well as tumor-related pathways between low- and high-risk groups according to the established ferroptosis-related signature model in HCC.…”
Section: The Translation Of Ferroptosis Into Clinical Hcc Practicementioning
confidence: 99%
“…Another approach is based on the interaction of ferroptosis and either long noncoding RNAs (lncRNAs) or miRNA as identified via in silico [ 116 , 117 , 124 ] or via in vitro/in vivo analyses [ 125 ].…”
Section: The Translation Of Ferroptosis Into Clinical Hcc Practicementioning
confidence: 99%
See 1 more Smart Citation